Secondary battery and electric equipment
By setting a layer of lithium iron phosphate material in specific position sequence and particle size distribution on the positive electrode current collector, and combining with the carbon layer, the performance bottleneck of lithium iron phosphate material in ultrafast charging and high power is solved, and the balance of fast charging performance, power performance, cycle performance and energy density is achieved.
Patent Information
- Application Number
- CN202411518374.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-28
AI Technical Summary
Lithium iron phosphate materials are limited in ultrafast charging and high power, and nano-treatment results in high specific surface area of particles, low compaction density, high chemical reaction activity, resulting in poor high-temperature circulation and storage stability and fast capacity attenuation.
The first and second lithium iron phosphate positive electrode active material layers with specific position sequence and particle size distribution are used, combined with the carbon layer, and the structure and composition of the positive electrode sheet are optimized to improve conductivity and lithium ion transport capability.
The balance of fast charging performance, power performance, cycle performance and energy density of secondary batteries is achieved, and the overall performance of the battery is improved.
Smart Images

Figure CN119542506A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of new energy technology and relates to a secondary battery and electrical equipment. Background Art
[0002] Lithium iron phosphate materials are low-cost and highly safe, but they have poor electronic conductivity and one-dimensional lithium ion diffusion coefficient, which limits them in terms of ultra-fast charging and high power. The method to improve the conductivity of lithium iron phosphate materials can be to coat them with carbon; the method to improve the lithium ion transmission capacity of lithium iron phosphate materials can be to reduce the particle radius of lithium iron phosphate materials and make them nano-sized. Usually, the average radius of high-rate or fast-charging lithium iron phosphate positive electrode materials is between 100nm and 1000nm.
[0003] Although the use of nanosized small particles alone can significantly improve the fast charging rate performance, it will also cause the particles to have a high specific surface area, which will result in low compaction density and high chemical reaction activity of the electrode prepared using them, leading to a series of problems such as poor high-temperature cycling and storage stability, and rapid capacity decay.
[0004] The method of mixing a certain proportion of large particles with nano-sized particles can balance energy density and fast charging performance, but this method is difficult to fully exert the fast charging performance and high power performance of lithium iron phosphate. Therefore, it is urgent to develop a technology to better exert the fast charging performance and high power performance of lithium iron phosphate. Summary of the invention
[0005] Based on the defects of the prior art, the purpose of this application is to provide a secondary battery and an electrical device.
[0006] In order to achieve the above-mentioned object, in a first aspect, the present application provides a secondary battery, including a positive electrode sheet, wherein the positive electrode sheet includes:
[0007] Positive electrode current collector;
[0008] A first positive electrode active material layer is located on at least one side of the positive electrode current collector and comprises a first lithium iron phosphate, wherein the Dv50 of the first lithium iron phosphate is 800 to 1000 nm, the Dv10 is 200 to 500 nm, and the Dv90 is 2000 to 4000 nm;
[0009] The second positive electrode active material layer is located on the surface of the first positive electrode active material away from the positive electrode current collector and comprises a second lithium iron phosphate. The second lithium iron phosphate has a Dv50 of 100 to 200 nm, a Dv10 of 30 to 80 nm, and a Dv90 of 400 to 800 nm.
[0010] In some embodiments of the present application, the thickness of the first positive electrode active material layer is h 1, the thickness of the second positive electrode active material layer is h 2 , 0.15≤h 2 / (h 1 +h 2 )≤0.35.
[0011] In some embodiments of the present application, the sum of the single-surface density of the first positive electrode active material layer and the second positive electrode active material layer is 12 to 32 mg / cm 2 .
[0012] In some embodiments of the present application, the mass fraction of the first lithium iron phosphate in the first positive electrode active material layer is 95% to 98%; and / or
[0013] The mass fraction of the second lithium iron phosphate in the second positive electrode active material layer is 95% to 98%.
[0014] In some embodiments of the present application, the positive electrode sheet further includes a carbon layer, and the carbon layer is located on a surface of the second positive electrode active material facing away from the positive electrode current collector.
[0015] In some embodiments of the present application, the carbon layer comprises at least one of soft carbon, hard carbon, and graphite.
[0016] In some embodiments of the present application, the thickness of the carbon layer is 100 nm to 10 μm.
[0017] In some embodiments of the present application, the compaction density of the positive electrode sheet is 2.5 to 2.65 g / cm 3 .
[0018] In some embodiments of the present application, at least one of the following conditions is met:
[0019] (1) The gram capacity of the first lithium iron phosphate and the second lithium iron phosphate are independently ≥ 155 mAh / g;
[0020] (2) The thickness of the positive electrode sheet is 100 to 270 μm;
[0021] (3) The thickness of the positive electrode current collector is 8 to 16 μm.
[0022] In a second aspect, the present application further provides an electrical device, comprising the secondary battery, wherein the secondary battery is used as a power supply for the electrical device.
[0023] Compared with the prior art, the beneficial effect of the present application is that the present application improves the fast charging performance and power performance of the secondary battery by arranging the first positive electrode active material layer and the second positive electrode active material layer with a specific position order and a specific lithium iron phosphate particle size distribution on the positive electrode current collector, thereby achieving a balance among the fast charging performance, power performance, cycle performance and energy density. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Schematic diagram of the structure of the positive electrode plate in Example 1, wherein 101 is aluminum foil, 102 is a first positive electrode active material layer, 103 is a second positive electrode active material layer, 104 is a carbon layer, and 105 is a mixture of a binder and a conductive agent in the first positive electrode active material layer. DETAILED DESCRIPTION
[0025] In order to better illustrate the purpose, technical scheme and advantages of the present application, the present application will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present application in detail, rather than to limit the present application. All other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application. The experimental reagents and instruments involved in the implementation of this application are all commonly used ordinary reagents and instruments unless otherwise specified. In the present application, the technical features described in an open manner include closed technical schemes composed of the listed features, and also include open technical schemes containing the listed features.
[0026] The present application provides a secondary battery, including a positive electrode sheet, the positive electrode sheet including:
[0027] Positive electrode current collector;
[0028] A first positive electrode active material layer is located on at least one side of the positive electrode current collector and comprises a first lithium iron phosphate, wherein the first lithium iron phosphate has a Dv50 of 800 to 1000 nm, a Dv10 of 200 to 500 nm, and a Dv90 of 2000 to 4000 nm;
[0029] The second positive electrode active material layer is located on the surface of the first positive electrode active material away from the positive electrode current collector and comprises a second lithium iron phosphate. The second lithium iron phosphate has a Dv50 of 100 to 200 nm, a Dv10 of 30 to 80 nm, and a Dv90 of 400 to 800 nm.
[0030] When the Dv10, Dv50 and Dv90 of the first lithium iron phosphate in the first positive electrode active material layer are selected within the above-mentioned specific range, the larger particles and smaller particles in the first lithium iron phosphate will stack with each other to make the stacking more compact and the gap smaller, which is beneficial to improve the overall compaction density of the positive electrode plate, improve the volume energy density, and help improve the high temperature stability. When the Dv10, Dv50 and Dv90 of the second lithium iron phosphate in the second positive electrode active material layer are selected within the above-mentioned specific range, the gaps between the second lithium iron phosphate particles are more uniform, and the second positive electrode active material layer has more mesh pores, which is beneficial to the infiltration of the electrolyte, the increase of the liquid retention and the lithium insertion and deintercalation channels, and can reduce the side reactions between the second lithium iron phosphate particles and the electrolyte; at the same time, the overall particle size of the second lithium iron phosphate is smaller, so that the ion transmission path of the second positive electrode active material layer is shorter, and the lithium ion deintercalation polarization is smaller, which is beneficial to the rapid storage of lithium and the diffusion of lithium ions to the first positive electrode active material layer, and the role of a "bridge" for lithium ion transmission is realized.
[0031] The above-mentioned secondary battery breaks the bottleneck of fast charging performance and power performance of the secondary battery by arranging the first positive electrode active material layer and the second positive electrode active material layer with a specific position order and a specific lithium iron phosphate particle size distribution on the positive electrode current collector, so as to better balance the fast charging performance, power performance, cycle performance and energy density.
[0032] The Dv50 of the first lithium iron phosphate is 800-1000 nm, such as 800 nm, 850 nm, 900 nm, 950 nm, 1000 nm or a range formed by any two of the above values.
[0033] The Dv10 of the first lithium iron phosphate is 200-500 nm, such as 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm or a range formed by any two of the above values.
[0034] The Dv90 of the first lithium iron phosphate is 2000-4000 nm, such as 2000 nm, 2200 nm, 2500 nm, 2700 nm, 3000 nm, 3200 nm, 3500 nm, 3700 nm, 4000 nm or a range formed by any two of the above values.
[0035] The Dv50 of the second lithium iron phosphate is 100-200 nm, such as 100 nm, 120 nm, 140 nm, 160 nm, 180 nm, 200 nm or a range formed by any two of the above values.
[0036] The Dv10 of the second lithium iron phosphate is 30-80 nm, such as 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm or a range formed by any two of the above values.
[0037] The Dv90 of the second lithium iron phosphate is 400-800 nm, such as 400 nm, 500 nm, 600 nm, 700 nm, 800 nm or a range formed by any two of the above values.
[0038] The Dv10, Dv50 and Dv90 of the first lithium iron phosphate and the second lithium iron phosphate can be measured and obtained by a powder laser particle size tester.
[0039] In some embodiments of the present application, the thickness of the first positive electrode active material layer is h 1 , the thickness of the second positive electrode active material layer is h 2 , 0.15≤h 2 / (h 1 +h 2 )≤0.35. By controlling h 2 / (h 1 +h 2 ) is within the range of 0.15 to 0.35, such as 0.15, 0.17, 0.20, 0.22, 0.25, 0.27, 0.30, 0.32, 0.35 or a range formed by any two of the above values, so as to obtain higher energy density and better power performance and cycle performance while making fast charging performance better. h 1 and h 2 The units of are the same and both can be obtained through scanning electron microscope measurement.
[0040] In some embodiments of the present application, the sum of the single-surface density (CW) of the first positive electrode active material layer and the second positive electrode active material layer is 12 to 32 mg / cm 2 The sum of the single-surface density of the first positive electrode active material layer and the second positive electrode active material layer is controlled to be between 12 and 32 mg / cm 2 In the range of 16-22 mg / cm 2 Within this range, it is beneficial for the positive electrode to obtain a higher energy density while shortening the lithium ion migration path, reducing impedance and polarization, and improving rate performance, thereby significantly improving fast charging capability and power performance. The sum of the single-sided surface density of the first positive electrode active material layer and the second positive electrode active material layer can be selected to be 12 mg / cm 2 、14mg / cm 2 、16mg / cm 2 、18mg / cm 2 , 20mg / cm 2 , 22mg / cm 2 , 24mg / cm 2 、26mg / cm 2 、28mg / cm 2 、30mg / cm 2 、32mg / cm2 Or the range formed by any two of the above values.
[0041] The sum of the single-surface density of the first positive electrode active material layer and the second positive electrode active material layer (CW) can be measured by the small disc weighing method: take the positive electrode sheet and cut it into small discs, weighing it as m1; use NMP (N-methylpyrrolidone) to wipe off the first positive electrode active material layer and the second positive electrode active material layer on the small disc, weighing it as m0, that is, the mass of the foil; the single-surface area of the test small disc is s1. CW = (m1-m0) / (2*s1).
[0042] In some embodiments of the present application, the single-surface density of the first positive electrode active material layer is 10.8 to 28.8 mg / cm 2 , such as 10.8mg / cm 2 , 12mg / cm 2 、14mg / cm 2 、16mg / cm 2 、18mg / cm 2 , 20mg / cm 2 , 22mg / cm 2 , 24mg / cm 2 , 26mg / cm 2 、28mg / cm 2 、28.8mg / cm 2 Or the range formed by any two of the above values, so as to make the cycle performance, high temperature stability, energy density and processing performance of the positive electrode sheet better.
[0043] In some embodiments of the present application, the single-surface density of the second positive electrode active material layer is 1.2 to 8 mg / cm 2 , such as 1.2mg / cm 2 , 2mg / cm 2 、3mg / cm 2 , 4mg / cm 2 , 5mg / cm 2 , 6mg / cm 2 , 7mg / cm 2 , 8mg / cm 2 Or the range formed by any two of the above values, so that the fast charging performance and power performance of the positive electrode plate are better.
[0044] In some embodiments of the present application, the mass fraction of the first lithium iron phosphate in the first positive electrode active material layer is 95% to 98%. The mass fraction of the first lithium iron phosphate in the first positive electrode active material layer is controlled within the range of 95% to 98%, such as 95%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98% or a range formed by any two of the above values, and the proportion of lithium iron phosphate active material is increased as much as possible under the premise of ensuring the conductivity and bonding performance of the pole piece, so as to improve the energy density.
[0045] In some embodiments of the present application, the first positive electrode active material layer further includes a conductive agent. Exemplarily, the conductive agent in the first positive electrode active material layer includes at least one of conductive carbon black (SP), carbon nanotubes, and graphene.
[0046] In some embodiments of the present application, the mass fraction of the conductive agent in the first positive electrode active material layer is 0.5% to 2.5%, such as 0.5, 1%, 1.5%, 2%, 2.5% or a range formed by any two of the above values.
[0047] In some embodiments of the present application, the first positive electrode active material layer further includes a binder. Exemplarily, the binder in the first positive electrode active material layer includes at least one of PVDF (polyvinylidene fluoride), PAA (polyacrylic acid), PI (polyimide), and PMMA (polymethyl methacrylate).
[0048] In some embodiments of the present application, the mass fraction of the binder in the first positive electrode active material layer is 0.5% to 2.5%, such as 0.5, 1%, 1.5%, 2%, 2.5% or a range formed by any two of the above values.
[0049] In some embodiments of the present application, the mass fraction of the second lithium iron phosphate in the second positive electrode active material layer is 95% to 98%. The mass fraction of the second lithium iron phosphate in the second positive electrode active material layer is controlled to be within the range of 95% to 98%, such as 95%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98% or a range formed by any two of the above values.
[0050] In some embodiments of the present application, the second positive electrode active material layer further comprises a conductive agent. Exemplarily, the conductive agent in the second positive electrode active material layer comprises at least one of conductive carbon black, carbon nanotubes, and graphene.
[0051] In some embodiments of the present application, the mass fraction of the conductive agent in the second positive electrode active material layer is 0.5% to 2.5%, such as 0.5%, 1%, 1.5%, 2%, 2.5% or a range formed by any two of the above values.
[0052] In some embodiments of the present application, the second positive electrode active material layer further includes a binder. Exemplarily, the binder in the second positive electrode active material layer includes at least one of PVDF, PAA (polyacrylic acid), PI (polyimide), and PMMA (polymethyl methacrylate).
[0053] In some embodiments of the present application, the mass fraction of the binder in the second positive electrode active material layer is 0.5% to 2.5%, such as 0.5%, 1%, 1.5%, 2%, 2.5% or a range formed by any two of the above values.
[0054] In some embodiments of the present application, the positive electrode plate further includes a carbon layer, which is located on the surface of the second positive electrode active material facing away from the positive electrode current collector. Providing a carbon layer on the surface of the second positive electrode active material facing away from the positive electrode current collector can not only increase the liquid retention of the surface layer of the positive electrode plate and form a more stable SEI layer, but also the carbon layer can serve as a carrier for desolvation of lithium ions from the electrolyte, thereby improving the one-dimensional lithium conduction path of lithium iron phosphate to two dimensions or even higher dimensions, improving the lithium ion conduction at the liquid-solid interface, and significantly improving the multiple charge and discharge performance. Exemplarily, the carbon layer comprises at least one of soft carbon, hard carbon, and graphite.
[0055] In some embodiments of the present application, the thickness of the carbon layer is 100nm to 10μm. The thickness of the carbon layer is controlled within the range of 100nm to 10μm, such as 100nm, 200nm, 500nm, 800nm, 1μm, 3μm, 5μm, 7μm, 10μm or a range formed by any two of the above values, so that the positive electrode sheet has a better liquid retention coefficient and lithium conductivity. The thickness of the carbon layer can be adjusted within the above-mentioned carbon layer thickness range according to the actual fast charging requirements and equipment production capacity. The thickness of the carbon layer can be obtained by scanning electron microscopy measurement.
[0056] In some embodiments of the present application, the carbon layer comprises a carbon source, a conductive agent, a thickener and a binder. The carbon source in the carbon layer may be selected to include at least one of soft carbon and graphene; the conductive agent in the carbon layer may be selected to include at least one of CNT (carbon nanotube) and carbon black; the thickener in the carbon layer may be selected to include at least one of CMC (carboxymethyl cellulose) and polyurethane; the binder in the carbon layer may be selected to include at least one of PAA (polyacrylic acid) and SBR (styrene-butadiene rubber).
[0057] In one embodiment of the present application, the mass fraction of the carbon source in the carbon layer is 80% to 90%, such as 80%, 82%, 84%, 86%, 88%, 90% or a range formed by any two of the above values.
[0058] In one embodiment of the present application, the mass fraction of the conductive agent in the carbon layer is 2.5% to 5%, such as 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or a range formed by any two of the above values.
[0059] In one embodiment of the present application, the mass fraction of the thickener in the carbon layer is 2.5% to 5%, such as 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or a range formed by any two of the above values.
[0060] In one embodiment of the present application, the mass fraction of the binder in the carbon layer is 5% to 10%, such as 5%, 6%, 7%, 8%, 9%, 10% or a range formed by any two of the above values.
[0061] In some embodiments of the present application, the compaction density of the positive electrode sheet is 2.5 to 2.65 g / cm 3 . Control the compaction density (PD) of the positive electrode sheet at 2.5~2.65g / cm 3 In the range of 2.55-2.6 g / cm 3 When the positive electrode sheet is within the range, it has higher energy density and power performance. The compaction density of the positive electrode sheet can be selected as 2.5g / cm 3 , 2.52g / cm 3 , 2.55g / cm 3 , 2.57g / cm 3 , 2.6g / cm 3 , 2.62g / cm 3 , 2.65g / cm 3 Or the range formed by any two of the above values. The compaction density of the positive electrode sheet can be calculated according to the following formula: PD = 2*CW / h, which is equal to the surface density of the double-sided coating (i.e., the sum of the single-sided surface density of the first positive electrode active material layer and the second positive electrode active material layer CW) divided by the thickness h of the positive electrode active layer, and the thickness h of the positive electrode active layer = thickness of the positive electrode sheet - thickness of the positive electrode collector; the thickness of the positive electrode sheet and the thickness of the positive electrode collector can be measured by a micrometer or by scanning electron microscope.
[0062] In some embodiments of the present application, the gram capacity of the first lithium iron phosphate and the second lithium iron phosphate are independently ≥155mAh / g. The gram capacity of the first lithium iron phosphate is controlled to be ≥155mAh / g, especially when it is 158-161mAh / g, so that the capacity of the positive electrode plate is higher; the gram capacity of the second lithium iron phosphate is controlled to be ≥155mAh / g, especially when it is 158-161mAh / g, so that the capacity of the positive electrode plate is higher. The gram capacity of the first lithium iron phosphate and the gram capacity of the second lithium iron phosphate can both be the discharge capacity of the corresponding lithium iron phosphate to the lithium sheet composition.
[0063] In some embodiments of the present application, the thickness of the positive electrode sheet is 100 to 270 μm. The thickness of the positive electrode sheet is selected to be 100 to 270 μm, such as 100 μm, 120 μm, 140 μm, 160 μm, 180 μm, 200 μm, 220 μm, 240 μm, 260 μm, 270 μm or a range formed by any two of the above values, so that the positive electrode sheet is loaded with more active substances to improve the energy density of the battery. If it is too high, the rate performance of the battery will be sacrificed and the capacity will be reduced. The thickness of the positive electrode sheet can be obtained by scanning electron microscopy measurement, or it can be measured by a micrometer.
[0064] In some embodiments of the present application, the thickness of the positive electrode current collector is 8 to 16 μm. When the thickness of the positive electrode current collector is selected to be in the range of 8 to 16 μm, especially in the range of 10 to 12 μm, the positive electrode current collector has a smaller thickness while providing a higher flexural strength, and the energy density of the positive electrode sheet is higher. The thickness of the positive electrode current collector can be selected to be 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, or a range formed by any two of the above values. The thickness of the positive electrode current collector can be obtained by scanning electron microscopy measurement, or it can be measured by a micrometer.
[0065] In some embodiments of the present application, the positive electrode current collector includes at least one of aluminum foil (uncoated with carbon) and carbon-coated aluminum foil. The carbon layer thickness of the carbon-coated aluminum foil is ≤ 2 μm, such as 2 μm, 1.5 μm, 1.0 μm, 0.5 μm, 0.1 μm or a range formed by any two of the above values.
[0066] In some embodiments of the present application, the method for preparing the positive electrode sheet comprises the following steps:
[0067] Dispersing the first lithium iron phosphate, the binder and the conductive agent in a solvent to obtain a first positive electrode active material layer slurry;
[0068] Dispersing the second lithium iron phosphate, the binder and the conductive agent in a solvent to obtain a second positive electrode active material layer slurry;
[0069] The first positive electrode active material layer slurry and the second positive electrode active material layer slurry are coated on at least one side of the positive electrode current collector, dried, rolled, slit, and cut to obtain a positive electrode sheet.
[0070] In one embodiment, in the first positive electrode active material layer slurry, the Dv50 of the first lithium iron phosphate is 800-1000 nm, the Dv10 is 200-500 nm, and the Dv90 is 2000-4000 nm.
[0071] In one embodiment, the preparation method of the first lithium iron phosphate includes the following steps: weighing an iron source, a lithium source, a phosphorus source and a carbon source, mixing, and drying, wherein the iron source, the lithium source, the phosphorus source and the carbon source are weighed in a stoichiometric ratio of 1:1:1, and the carbon source is weighed at 1% to 2.5% of the mass of the theoretically produced lithium iron phosphate, and then sintering at 300 to 350°C for 5 to 10 hours in an inert atmosphere to preliminarily decompose the raw materials, and then sintering at 600 to 800°C for 10 to 48 hours to obtain olivine-type lithium iron phosphate, and then crushing and screening the obtained olivine-type lithium iron phosphate to obtain the first lithium iron phosphate. Among them, the lithium source can be selected to include at least one of lithium carbonate, lithium hydroxide, and lithium dihydrogen phosphate; the iron source can be selected to include at least one of ferrous oxalate, ferrous oxalate, red iron oxide, and iron phosphate; the carbon source can be selected to include at least one of sucrose, graphite, starch, and glucose; the phosphorus source can be selected to include at least one of ammonium hydrogen phosphate, phosphoric acid, ammonium dihydrogen phosphate, and iron phosphate.
[0072] In one embodiment, in the first positive electrode active material layer slurry, the conductive agent includes at least one of conductive carbon black, carbon nanotubes, and graphene.
[0073] In one embodiment, in the first positive electrode active material layer slurry, the binder includes at least one of PVDF, PAA (polyacrylic acid), PI (polyimide), and PMMA (polymethyl methacrylate).
[0074] In one embodiment, in the first positive electrode active material layer slurry, the mass of the first lithium iron phosphate is M 1 , the mass of the conductive agent is M 2 , the mass of the binder is M 3 , 95%≤M 1 / (M 1 +M 2 +M 3 )≤98%,0.5%≤M 2 / (M 1 +M 2 +M 3 )≤2.5%,0.5%≤M 3 / (M 1 +M 2 +M 3 )≤2.5%.
[0075] In one embodiment, in the first positive electrode active material layer slurry, the solvent includes at least one of NMP and deionized water.
[0076] In one embodiment, the solid content of the first positive electrode active material layer slurry is 60 wt.% to 70 wt.%.
[0077] In one embodiment, in the second positive electrode active material layer slurry, the second lithium iron phosphate has a Dv50 of 100 to 200 nm, a Dv10 of 30 to 80 nm, and a Dv90 of 400 to 800 nm.
[0078] In one embodiment, the preparation method of the second lithium iron phosphate includes the following steps: weighing an iron source, a lithium source, a phosphorus source and a carbon source, mixing, and drying, wherein the iron source, the lithium source, the phosphorus source and the carbon source are weighed in a stoichiometric ratio of 1:1:1, and the carbon source is weighed at 1% to 2.5% of the mass of the theoretically produced lithium iron phosphate, and then sintering at 300 to 350°C for 5 to 10 hours in an inert atmosphere to preliminarily decompose the raw materials, and then sintering at 600 to 800°C for 10 to 48 hours to obtain olivine-type lithium iron phosphate, and then crushing and screening the obtained olivine-type lithium iron phosphate to obtain the second lithium iron phosphate. Among them, the lithium source can be selected to include at least one of lithium carbonate, lithium hydroxide, and lithium dihydrogen phosphate; the iron source can be selected to include at least one of ferrous oxalate, ferrous oxalate, red iron oxide, and iron phosphate; the carbon source can be selected to include at least one of sucrose, graphite, starch, and glucose; the phosphorus source can be selected to include at least one of ammonium hydrogen phosphate, phosphoric acid, ammonium dihydrogen phosphate, and iron phosphate.
[0079] In one embodiment, in the second positive electrode active material layer slurry, the conductive agent includes at least one of conductive carbon black, carbon nanotubes, and graphene.
[0080] In one embodiment, in the second positive electrode active material layer slurry, the binder includes at least one of PVDF, PAA (polyacrylic acid), PI (polyimide), and PMMA (polymethyl methacrylate).
[0081] In one embodiment, in the second positive electrode active material layer slurry, the mass of the first lithium iron phosphate is m 1 , the mass of the conductive agent is m 2 , the mass of the binder is m 3 , 95%≤m 1 / (m 1 +m 2 +m 3 )≤98%,0.5%≤m 2 / (m 1 +m 2 +m 3 )≤2.5%,0.5%≤m 3 / (m 1 +m 2 +m 3 )≤2.5%.
[0082] In one embodiment, in the second positive electrode active material layer slurry, the solvent includes at least one of NMP and deionized water.
[0083] In one embodiment, the solid content of the second positive electrode active material layer slurry is 60 wt.% to 70 wt.%.
[0084] In one embodiment, the method for preparing the positive electrode sheet further includes the following steps: spraying a carbon layer after drying and before rolling.
[0085] The carbon layer can be formed by spraying a carbon layer slurry. The carbon layer slurry can optionally contain a carbon source, a conductive agent, a thickener, a binder, and a solvent. The carbon source in the carbon layer slurry can be selected to include at least one of soft carbon and graphene; the conductive agent in the carbon layer slurry can be selected to include at least one of CNT (carbon nanotube) and carbon black; the thickener in the carbon layer slurry can be selected to include at least one of CMC (carboxymethyl cellulose) and polyurethane; the binder in the carbon layer slurry can be selected to include at least one of PAA (polyacrylic acid) and SBR (styrene-butadiene rubber); the solvent in the carbon layer slurry can be selected to include at least one of deionized water and NMP.
[0086] Based on the total weight of the carbon source, conductive agent, thickener and binder in the carbon layer slurry, the weight of the carbon source can be selected to be 80% to 90%, such as 80%, 82%, 84%, 86%, 88%, 90% or a range formed by any two of the above values; the mass fraction of the conductive agent is 2.5% to 5%, such as 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or a range formed by any two of the above values; the mass fraction of the thickener is 2.5% to 5%, such as 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or a range formed by any two of the above values; the mass fraction of the binder is 5% to 10%, such as 5%, 6%, 7%, 8%, 9%, 10% or a range formed by any two of the above values. The solid content of the carbon layer slurry can be selected to be 50wt.% to 60wt.%, such as 50wt.%, 52wt.%, 54wt.%, 56wt.%, 58wt.%, 60wt.% or a range formed by any two of the above values.
[0087] The secondary battery also includes a negative electrode plate. The present application has no special restrictions on the negative electrode plate, and any commonly used negative electrode plate in the art can be used.
[0088] In some embodiments of the present application, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode active material, a conductive agent, a dispersant and a binder.
[0089] In one embodiment, the negative electrode active material may include at least one of graphite, silicon carbon, silicon oxygen, or a combination thereof.
[0090] In one embodiment, the mass fraction of the negative electrode active material in the negative electrode active material layer may be selected to be 96% to 98%.
[0091] In one embodiment, the conductive agent may include at least one of conductive carbon black (SP), carbon nanotubes, and graphene.
[0092] In one embodiment, the mass fraction of the conductive agent in the negative electrode active material layer may be selected to be 1% to 1.8%.
[0093] In one embodiment, the thickener may be selected to include at least one of sodium carboxymethyl cellulose (CMC-Na) and lithium carboxymethyl cellulose (CMC-Li).
[0094] In one embodiment, the mass fraction of the dispersant in the negative electrode active material layer may be selected to be 0.5% to 1.2%.
[0095] In one embodiment, the binder may be selected to include at least one of styrene-butadiene rubber (SBR) and PAA (polyacrylic acid).
[0096] In one embodiment, the mass fraction of the binder in the negative electrode active material layer may be selected to be 0.5% to 1%.
[0097] In one embodiment, the single surface density of the negative electrode active material layer can be selected to be 100 to 160 mg / cm 2 .
[0098] In one embodiment, the compaction density of the negative electrode sheet can be selected to be 1.5-1.6 g / cm 3 .
[0099] In one embodiment, the negative electrode current collector may include at least one of copper foil and composite copper foil.
[0100] In one embodiment, the thickness of the negative electrode current collector may be selected to be 4.5-8 μm.
[0101] There is no limitation on the preparation method of the negative electrode sheet, and the negative electrode sheet can be prepared according to conventional methods in the art, such as dispersing the negative electrode active material, conductive agent, dispersant and binder in a solvent to form a negative electrode slurry, coating the negative electrode slurry on the negative electrode current collector, and obtaining the negative electrode sheet through drying, rolling and other processes. The solvent in the negative electrode slurry can be selected as at least one of deionized water. The solid content of the negative electrode slurry can be selected as 45wt.% to 55wt.%.
[0102] In some embodiments of the present application, the secondary battery further comprises a separator. The present application has no limitation on the separator, and any commonly used separator in the art may be used. Exemplarily, the separator comprises at least one of polyethylene, polypropylene, polyvinylidene fluoride, and the like.
[0103] In some embodiments of the present application, the secondary battery further comprises an electrolyte. The present application has no limitation on the electrolyte, and any commonly used electrolyte in the art may be used. In one embodiment, the electrolyte comprises a lithium salt and a solvent, and the lithium salt may include lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ) and lithium trifluoromethanesulfonate (LiCF 3 SO 3 ), the concentration of lithium salt in the electrolyte can be selected to be 0.8-1.5 mol / L; the solvent can be selected to include at least one of ethylene carbonate (EC), polycarbonate (PC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC), sulfite, and carboxylate, and the mass fraction of the solvent in the electrolyte can be selected to be 75%-85%. The electrolyte can also contain additives, and the additives can be selected to include at least one of a negative electrode film-forming agent, a positive electrode film-forming agent, an overcharge protection additive, a high and low temperature additive, and a flame retardant additive.
[0104] In some embodiments of the present application, a method for preparing a secondary battery comprises the following steps:
[0105] The positive electrode sheet, the negative electrode sheet and the separator are assembled into a secondary battery by stacking or winding.
[0106] The present application also provides an electrical device, which includes the above-mentioned secondary battery, and the above-mentioned secondary battery is used as a power supply for the electrical device.
[0107] The present application is further described below through specific embodiments.
[0108] Example 1
[0109] This embodiment provides a secondary battery, and a method for preparing the secondary battery includes the following steps:
[0110] (1) Preparation of positive electrode sheet
[0111] (1.1) Weigh an iron source, a lithium source, a phosphorus source and a carbon source, mix them, and dry them. The iron source, the lithium source, the phosphorus source and the carbon source are weighed in a stoichiometric ratio of 1:1:1, and the carbon source is weighed at 1.5% of the mass of the theoretically produced lithium iron phosphate. Then, the mixture is sintered at 300° C. for 10 h in a nitrogen atmosphere and then sintered at 700° C. for 24 h, and then crushed and sieved to obtain the first lithium iron phosphate.
[0112] An iron source, a lithium source, a phosphorus source and a carbon source are weighed, mixed and dried, wherein the iron source, the lithium source, the phosphorus source and the carbon source are weighed in a stoichiometric ratio of 1:1:1, and the carbon source is weighed at 1.5% of the mass of the theoretically produced lithium iron phosphate. The mixture is then sintered at 300° C. for 10 h in a nitrogen atmosphere and then sintered at 650° C. for 15 h, and then crushed and sieved to obtain a second lithium iron phosphate.
[0113] Among them, the lithium source is lithium carbonate; the iron source is red iron oxide; the carbon source is sucrose; and the phosphorus source is ammonium hydrogen phosphate.
[0114] (1.2) adding the first lithium iron phosphate, the binder PVDF and the conductive agent SP in a mass ratio of X:(100-X) / 2:(100-X) / 2 into the solvent NMP for dispersion to obtain a first positive electrode active material layer slurry with a solid content of 65 wt.% (forming a first positive electrode active material layer);
[0115] The second lithium iron phosphate, the binder PVDF and the conductive agent SP are added to the solvent NMP in a mass ratio of X: (100-X) / 2: (100-X) / 2 and dispersed to obtain a second positive electrode active material layer slurry with a solid content of 65 wt.% (forming a second positive electrode active material layer);
[0116] according to Figure 1 The structure shown in the figure, the first positive electrode active material layer slurry and the second positive electrode active material layer slurry are coated on both sides of the positive electrode current collector by an extrusion coating device, and dried to obtain a semi-finished product, wherein the positive electrode current collector is a carbon-coated aluminum foil with a thickness of 12 μm, and the thickness of the carbon layer in the carbon-coated aluminum foil is 2 μm;
[0117] The carbon layer slurry is used to spray a carbon layer on both sides of the semi-finished product, and then rolled, slit, and cut to obtain a positive electrode sheet, wherein the preparation method of the carbon layer slurry is as follows: soft carbon, CNT, CMC and PAA are mixed in a weight ratio of 85:4:4:7, and deionized water is added to obtain a carbon layer slurry with a solid content of 55wt.%;
[0118] Dv10, Dv50 and Dv90, X value, h of the first lithium iron phosphate and the second lithium iron phosphate 2 / (h 1 +h 2 ) value (the thickness of the first positive electrode active material layer is h 1 , the thickness of the second positive electrode active material layer is h 2 ,h 1 and h 2 The units are all mm), the total coating weight of the LFP layer (i.e., the sum of the single-surface surface densities of the first positive electrode active material layer and the second positive electrode active material layer), and the thickness of the carbon layer are shown in Table 1.
[0119] (2) Preparation of negative electrode sheet
[0120] Graphite, conductive carbon black (SP), sodium carboxymethyl cellulose (CMC-Na) and binder styrene-butadiene rubber (SBR) were added into deionized water in a mass ratio of 96:1:1:2 to obtain a negative electrode slurry with a solid content of 51 wt.%;
[0121] According to the single surface density of 130mg / cm 2 The negative electrode slurry is coated on both sides of the negative electrode current collector through an extrusion coating device, and rolled to obtain a negative electrode sheet, wherein the negative electrode current collector has a thickness of 6 μm.
[0122] (3) Preparation of electrolyte
[0123] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (EDC) were mixed in a volume ratio of 1:1:1, and then 1 mol / L LiPF 6 Mix and disperse to prepare an electrolyte.
[0124] (4) Preparation of secondary batteries
[0125] The positive electrode sheet, separator and negative electrode sheet are stacked in order, and a polyethylene film is selected as the separator, so that the separator is placed between the positive and negative electrode sheets to play an isolating role, and a stacked bare cell is obtained. The bare cell is placed in a punched aluminum-plastic film for packaging, and a secondary battery is obtained after liquid injection and formation to a fixed capacity.
[0126] Embodiments 2 to 5
[0127] Embodiments 2 to 5 all provide a secondary battery. The difference between the preparation methods of these secondary batteries and those of embodiment 1 is that the coating amounts of the first positive electrode active material layer slurry and the second positive electrode active material layer slurry are adjusted to adjust h 2 / (h 1 +h 2 ) value, specific h 2 / (h 1 +h 2 ) values are shown in Table 1.
[0128] Example 6
[0129] This embodiment provides a secondary battery. The difference between the preparation method of the secondary battery and that of Embodiment 1 is that the preparation methods of the first lithium iron phosphate and the second lithium iron phosphate are different. The specific differences are as follows:
[0130] In the process of preparing the first lithium iron phosphate, the lithium iron phosphate was first sintered at 300° C. for 10 h and then sintered at 720° C. for 24 h in a nitrogen atmosphere;
[0131] In the process of preparing the second lithium iron phosphate, the sintering is first performed at 300° C. for 10 h and then at 680° C. for 18 h in a nitrogen atmosphere;
[0132] The lithium source used in the preparation of the first lithium iron phosphate and the second lithium iron phosphate is lithium carbonate; the iron source and phosphorus source are iron phosphate; and the carbon source is glucose.
[0133] The Dv10, Dv50 and Dv90 of the first lithium iron phosphate and the second lithium iron phosphate obtained are shown in Table 1.
[0134] Example 7
[0135] This embodiment provides a secondary battery. The difference between the preparation method of the secondary battery and that of Embodiment 1 is that the preparation methods of the first lithium iron phosphate and the second lithium iron phosphate are different. The specific differences are as follows:
[0136] In the process of preparing the first lithium iron phosphate, the lithium iron phosphate was first sintered at 300° C. for 10 h and then sintered at 710° C. for 24 h in a nitrogen atmosphere;
[0137] In the process of preparing the second lithium iron phosphate, the material is first sintered at 300° C. for 10 h and then sintered at 660° C. for 15 h in a nitrogen atmosphere;
[0138] The lithium source used in the preparation of the first lithium iron phosphate and the second lithium iron phosphate is lithium carbonate; the iron source and phosphorus source are iron phosphate; and the carbon source is glucose.
[0139] The Dv10, Dv50 and Dv90 of the first lithium iron phosphate and the second lithium iron phosphate obtained are shown in Table 1.
[0140] Embodiments 8 to 9
[0141] Embodiments 8 to 9 provide a secondary battery. The difference between the preparation methods of these secondary batteries and those of Embodiment 1 is that the value of X is adjusted, and the coating amount of the first positive electrode active material layer slurry and the second positive electrode active material layer slurry is adjusted to adjust the total coating weight of the LFP layer. The specific value of X and the total coating weight of the LFP layer are shown in Table 1.
[0142] The coating amount of the carbon layer is adjusted to adjust the thickness of the carbon layer. The specific thickness of the carbon layer is shown in Table 1.
[0143] Embodiments 10 to 11
[0144] Examples 10 to 11 all provide a secondary battery. The difference between the preparation methods of these secondary batteries and Example 1 is that the coating amount of the carbon layer is adjusted to adjust the thickness of the carbon layer. The specific thickness of the carbon layer is shown in Table 1.
[0145] Example 12
[0146] This embodiment provides a secondary battery. The difference between the preparation method of the secondary battery and that of Embodiment 1 is that no carbon layer is coated, that is, the thickness of the carbon layer is 0.
[0147] Comparative Example 1
[0148] This comparative example provides a secondary battery. The difference between the preparation method of the secondary battery in the comparative example and that in Example 1 is that the preparation methods of the first lithium iron phosphate and the second lithium iron phosphate are different. The specific differences are as follows:
[0149] In the process of preparing the first lithium iron phosphate, the lithium iron phosphate was first sintered at 350° C. for 10 h and then sintered at 750° C. for 40 h in a nitrogen atmosphere;
[0150] In the process of preparing the second lithium iron phosphate, the mixture is first sintered at 350° C. for 10 h and then sintered at 660° C. for 20 h in a nitrogen atmosphere;
[0151] The lithium source used in the preparation of the first lithium iron phosphate and the second lithium iron phosphate is lithium dihydrogen phosphate; the iron source is ferrous oxalate; the phosphorus source is phosphoric acid; and the carbon source is starch.
[0152] The Dv10, Dv50 and Dv90 of the first lithium iron phosphate and the second lithium iron phosphate obtained are shown in Table 1.
[0153] Comparative Example 2
[0154] This comparative example provides a secondary battery. The difference between the preparation method of the secondary battery in the comparative example and that in Example 1 is that the preparation methods of the first lithium iron phosphate and the second lithium iron phosphate are different. The specific differences are as follows:
[0155] In the process of preparing the first lithium iron phosphate, the lithium iron phosphate was first sintered at 320° C. for 10 h and then sintered at 700° C. for 20 h in a nitrogen atmosphere;
[0156] In the process of preparing the second lithium iron phosphate, the lithium iron phosphate was first sintered at 320° C. for 10 h and then sintered at 650° C. for 10 h in a nitrogen atmosphere;
[0157] The lithium source used in the preparation of the first lithium iron phosphate and the second lithium iron phosphate is lithium hydroxide; the iron source is ferrous oxalate; the phosphorus source is ammonium hydrogen phosphate; and the carbon source is glucose.
[0158] The Dv10, Dv50 and Dv90 of the first lithium iron phosphate and the second lithium iron phosphate obtained are shown in Table 1.
[0159] Comparative Example 3
[0160] This comparative example provides a secondary battery. The difference between the preparation method of the secondary battery in this comparative example and that in Example 1 is that the preparation method of the second lithium iron phosphate is different. The specific differences are as follows:
[0161] In the process of preparing the second lithium iron phosphate, a lithium source, an iron source, a phosphorus source and a carbon source are mixed in proportion, sintered at 310° C. for 10 hours and then at 650° C. for 20 hours in a nitrogen atmosphere;
[0162] The lithium source used in the preparation of the first lithium iron phosphate and the second lithium iron phosphate is lithium carbonate; the iron source is red iron oxide; the carbon source is sucrose; and the phosphorus source is ammonium dihydrogen phosphate.
[0163] The Dv10, Dv50 and Dv90 of the obtained second lithium iron phosphate are shown in Table 1.
[0164] Comparative Example 4
[0165] This comparative example provides a secondary battery. The difference between the preparation method of the secondary battery in this comparative example and that in Example 1 is that the preparation method of the first lithium iron phosphate is different. The specific differences are as follows:
[0166] In the process of preparing the first lithium iron phosphate, the lithium iron phosphate was first sintered at 310° C. for 10 h and then sintered at 700° C. for 15 h in a nitrogen atmosphere;
[0167] In the process of preparing the second lithium iron phosphate, the lithium iron phosphate was first sintered at 310° C. for 10 h and then sintered at 650° C. for 12 h in a nitrogen atmosphere;
[0168] The lithium source used in the preparation of the first lithium iron phosphate and the second lithium iron phosphate is lithium carbonate; the iron source is red iron oxide; the carbon source is sucrose; and the phosphorus source is ammonium dihydrogen phosphate.
[0169] The Dv10, Dv50 and Dv90 of the obtained first lithium iron phosphate are shown in Table 1.
[0170] Comparative Example 5
[0171] This comparative example provides a secondary battery. The difference between the preparation method of the secondary battery in this comparative example and that in Example 1 is that the steps of preparing the semi-finished product using the first positive electrode active material layer slurry and the second positive electrode active material layer are different, specifically as follows: In this comparative example, the first positive electrode active material layer slurry and the second positive electrode active material layer slurry are mixed according to the coating ratio of the two in Example 1 to obtain a positive electrode slurry, and then the obtained positive electrode slurry is coated on both sides of the positive electrode current collector through an extrusion coating device according to the total coating weight of the LFP layer in Example 1, and dried to obtain a semi-finished product.
[0172] Comparative Example 6
[0173] This comparative example provides a secondary battery. The difference between the preparation method of the secondary battery in the comparative example and that in Example 1 is that the first lithium iron phosphate and the second lithium iron phosphate are replaced in reverse.
[0174] The secondary batteries obtained in the above examples and comparative examples were subjected to the following performance tests:
[0175] (1) Fast charging capability test (MAS charging test)
[0176] The basis for the fast charging capability test is that during charging, as the active material of the negative electrode increases in lithium insertion, its potential will gradually decrease and eventually tend to 0V. When charging at a high rate, the polarization increases, causing the negative electrode potential to decrease. When it is lower than 0V, lithium deposition will occur. The fast charging test uses a three-electrode battery, in which the reference electrode is a lithium-plated copper wire attached between the positive and negative electrodes as the 0V potential. The lithium deposition potential, Verf, is confirmed by monitoring the potential of the copper wire and the negative electrode. Verf>0V means that the negative electrode is not lower than the lithium deposition potential and lithium deposition does not occur.
[0177] (1.1) Fixed volume
[0178] <1> 0.33C constant current charging to 3.8V, constant current constant voltage charging to 0.05C;
[0179] <2> Let stand for 10 minutes;
[0180] <3> 0.33C constant current discharge to 2.0V (the discharge capacity here is recorded as C0);
[0181] <4> Let stand for 10 minutes;
[0182] (1.2) Plating
[0183] <1> The positive and negative reference electrodes are charged with a current of 20uA for 2h;
[0184] (1.3) Fast charging test
[0185] Discharge in a high and low temperature box at 25±1℃: Verf is the negative electrode-reference electrode voltage, and V is the full battery voltage.
[0186] <1> 0.33C constant current discharge to 2.0V;
[0187] <2> Let stand for 30 minutes;
[0188] <3> 8C0 constant current charging until Verf≤0mV or V≥3.8V (charging capacity C1 in this step);
[0189] <4> 7C0 constant current charging until Verf≤0mV or V≥3.8V (charging capacity C2 in this step);
[0190] <5> 6C0 constant current charging until Verf≤0mV or V≥3.8V (charging capacity C3 in this step);
[0191] <6> 5C0 constant current charging until Verf≤0mV or V≥3.8V (charging capacity C4 in this step);
[0192] <7> 4C0 constant current charging until Verf≤0mV or V≥3.8V (charging capacity C5 in this step);
[0193] <8> 3C0 constant current charging until Verf≤0mV or V≥3.8V (charging capacity C6 in this step);
[0194] <9> 2C0 constant current charging until Verf≤0mV or V≥3.8V (charging capacity C7 in this step);
[0195] <10> 1C0 constant current charging until Verf≤0mV or V≥3.8V (charging capacity C9 in this step);
[0196] <13> 0.5C0 constant current charging until Verf≤0mV or V≥3.8V (this step charging capacity is C10);
[0197] <14> 0.1C0 constant current charging until Verf≤0mV or V≥3.8V (charging capacity C11 in this step);
[0198] <15> Let sit for 30 minutes.
[0199] The charging process from step 3 to step 14 is the fast charging capability test process, and its total time is t 总 (i.e. fast charging time), the total charging capacity is C 总 , fast charging time t 总 See Table 2.
[0200] Charging capacity percentage X1 = C1 / C 总 , X2~X8 are the same; X1~X8 calculated here are used for the following cycle capacity retention test.
[0201] (2) Cycle capacity retention test
[0202] At 25°C, the battery was charged at a constant current of 0.33C to 3.8V, then charged at a constant voltage of 3.8V to a current less than 0.05C. After standing for 5 minutes, the battery was discharged at a current of 0.33C to 2.0V to obtain a discharge capacity D.
[0203] Fast charging cycle test process:
[0204] <1> 8C0 constant current charging to X1 ratio of power;
[0205] <2> 7C0 constant current charging to X2 ratio;
[0206] <3> 6C0 constant current charging to X3 ratio of power;
[0207] <4> 5C0 constant current charging to X4 ratio;
[0208] <5> 4C0 constant current charging to X5 ratio;
[0209] <6> 3C0 constant current charging to X6 ratio;
[0210] <7> 2C0 constant current charging to X7 ratio;
[0211] <8> 1C0 constant current charging to X8 ratio;
[0212] <9> 0.33C constant current charging to 100% SOC;
[0213] <10> Let stand for 10 minutes;
[0214] <11> 1C constant current discharge to 0% SOC;
[0215] The test was stopped after the 1-11 steps were cycled until the capacity decayed to 80% of the initial discharge capacity.
[0216] The number of cycles is the number of cycles corresponding to the discharge capacity being 80% of the first cycle discharge capacity. The test results are shown in Table 2.
[0217] (3) Power performance test
[0218] <1> 1C constant current charging to 3.8V, constant current constant voltage charging to 0.05C;
[0219] <2> Let stand for 10 minutes;
[0220] <3> 0.33C constant current discharge to 2V (this step is 0.33C discharge capacity);
[0221] <4> Let stand for 10 minutes;
[0222] <5> 1C constant current charging to 3.8V, constant current constant voltage charging to 0.05C;
[0223] <6> Let stand for 10 minutes;
[0224] <7> 6C constant current discharge to 2V (this step is the capacity of 6C discharge);
[0225] <8> Let stand for 10 minutes;
[0226] Note: 6C discharge capacity retention rate = 6C discharge capacity / 0.33C discharge capacity × 100%.
[0227] (4) Interface status assessment
[0228] Full charge process: The battery after the cycle capacity retention test (2) is charged at a constant current of 0.33C to 3.8V, and then charged at a constant voltage of 0.05C, where C is the first discharge capacity at 0.33C.
[0229] Lithium plating degree: judged based on the surface color of the fully charged battery.
[0230] No lithium precipitation: pure yellow (golden yellow), no white-gray substance is visible to the naked eye.
[0231] Slight lithium deposition: a small amount of white or gray spots, with an area less than 1 / 10 of the electrode area.
[0232] Moderate lithium plating: Some white or gray spots, the area is less than 2 / 10 to 4 / 10 of the electrode area.
[0233] Severe lithium plating: Some white or gray spots, the area of which is larger than 4 / 10 of the electrode area.
[0234] Table 1
[0235]
[0236]
[0237] Table 2
[0238]
[0239] It can be seen from the above data that the secondary batteries obtained in each embodiment of the present application have good fast charging performance, power performance and cycle performance, and high energy density, such as fast charging time of less than 35min, 6C discharge retention rate of more than 82%, number of cycles of more than 3500, no lithium deposition or slight lithium deposition or moderate lithium deposition on the interface, and compaction density of 2.5g / cm 3 above.
[0240] In Comparative Example 1, the particle size of lithium iron phosphate in the first positive electrode active material layer and the second positive electrode active material layer is relatively large, resulting in deviations in fast charging performance, power performance, etc.
[0241] In Comparative Example 2, the particle size of lithium iron phosphate in the first positive electrode active material layer and the second positive electrode active material layer is relatively small, resulting in low compaction density, low energy density, and deviations in fast charging performance and cycle performance.
[0242] In Comparative Example 3, the particle size distribution of lithium iron phosphate in the second positive electrode active material layer is relatively wide, resulting in poor fast charging performance, power performance and cycle performance.
[0243] In Comparative Example 4, the particle size distribution of lithium iron phosphate in the first positive electrode active material layer is narrow, resulting in low compaction density and power performance deviation.
[0244] In Comparative Example 5, the positive electrode active material layer disposed on the positive electrode current collector is not a double layer, which causes deviation in the cycle performance.
[0245] In Comparative Example 6, the positions of the first positive electrode active material layer and the second positive electrode active material layer are unreasonable, which causes deviations in fast charging performance, power performance and cycle performance.
[0246] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.
Claims
1. A secondary battery, characterized in that: The invention comprises a positive electrode sheet, wherein the positive electrode sheet comprises: Positive electrode current collector; A first positive electrode active material layer is located on at least one side of the positive electrode current collector and comprises a first lithium iron phosphate, wherein the Dv50 of the first lithium iron phosphate is 800 to 1000 nm, the Dv10 is 200 to 500 nm, and the Dv90 is 2000 to 4000 nm; The second positive electrode active material layer is located on the surface of the first positive electrode active material away from the positive electrode current collector and comprises a second lithium iron phosphate. The second lithium iron phosphate has a Dv50 of 100 to 200 nm, a Dv10 of 30 to 80 nm, and a Dv90 of 400 to 800 nm.
2. The secondary battery according to claim 1, wherein: The thickness of the first positive electrode active material layer is h1, the thickness of the second positive electrode active material layer is h2, and 0.15≤h2 / (h1+h2)≤0.
35.
3. The secondary battery according to claim 1, wherein: The sum of the single-surface density of the first positive electrode active material layer and the second positive electrode active material layer is 12 to 32 mg / cm 2 .
4. The secondary battery according to claim 1, wherein: The mass fraction of the first lithium iron phosphate in the first positive electrode active material layer is 95% to 98%; and / or The mass fraction of the second lithium iron phosphate in the second positive electrode active material layer is 95% to 98%.
5. The secondary battery according to claim 1, wherein: The positive electrode sheet further includes a carbon layer, and the carbon layer is located on a surface of the second positive electrode active material facing away from the positive electrode current collector.
6. The secondary battery according to claim 5, characterized in that: The carbon layer includes at least one of soft carbon, hard carbon and graphite.
7. The secondary battery according to claim 5, characterized in that: The thickness of the carbon layer is 100 nm to 10 μm.
8. The secondary battery according to claim 1, wherein: The compaction density of the positive electrode sheet is 2.5 to 2.65 g / cm 3 .
9. The secondary battery according to claim 1, wherein: At least one of the following conditions is met: (1) The gram capacity of the first lithium iron phosphate and the second lithium iron phosphate are independently ≥ 155 mAh / g; (2) The thickness of the positive electrode sheet is 100 to 270 μm; (3) The thickness of the positive electrode current collector is 8 to 16 μm.
10. An electrical device, characterized in that: The invention comprises the secondary battery as claimed in any one of claims 1 to 9, wherein the secondary battery is used as a power supply for the electric device.
Citation Information
Patent Citations
Lithium-sulfur battery positive plate and preparation method thereof, and lithium-sulfur battery
CN109786748A
Lithium ion battery positive plate and lithium ion battery
CN116435466A
Positive pole piece, secondary battery, battery pack and electric equipment
CN117712283A
Positive plate and battery
CN117894922A
Secondary battery and electric device
CN118231579A
Cited By
Lithium ion secondary battery, battery device, power utilization device, preparation method of positive active material and preparation method of positive pole piece
CN120072865A
Lithium-ion secondary battery, battery apparatus, electrical apparatus, preparation method for positive electrode active material, and preparation method for positive electrode plate
US12706303B1